THE FACES OF THE DOUBLE IN MACHADO DE ASSIS AND AUGUSTO - Ana Paula da Costa (Travessias, 2007)
Machado de Assis is one of the biggest writers of the realism is considered and possesss a transcendental workmanship, to the step that Augusto Meyer is more had access as critical of that I eat poet. This work intends to privilege a study of a story of chats of Machado and a poem that composes the poetry of Meyer, being that both portray one of the subjects most common since the classic antiquity until modernity contemporary, the myth of the double one, the constant search of itself exactly, through consequences, either in the mirror or the water. To look itself is to come across itself with the other, the double one, the cindida identity, in way that the meeting with one to be definitive only remains as one I curl, and the double one if it imposes as one of leitmotivs that they designate it chats